A Rare Case of Thyrotoxic Periodic Paralysis in a Patient With Concomitant Methimazole-Induced Agranulocytosis - Kevin S. Wei, MD; Alexandra N. Lim, MD; Sophie M. Cannon, MD (AACE Clinical Case Reports)
Background/Objective: Thyrotoxic periodic paralysis (TPP) is a rare condition causing weakness of the lower extremities associated with significant hypokalemia. Likewise, agranulocytosis due to methimazole use is a rare occurrence. We present the first documented case of concomitant TPP and agranulocytosis from methimazole use. Case Report: A 48-year-old woman presented with sore throat, fevers, odynophagia, and sudden-onset bilateral leg weakness. Methimazole had been started 10 weeks prior for a new diagnosis of Graves’ disease. On admission, the patient was febrile, tachycardic, thyrotoxic, and neutropenic. She also experienced near-paralysis of the lower extremities. She was diagnosed with TPP and treated with beta blockade. She was admitted to the intensive care unit and started on broad-spectrum antibiotics, lithium, and propranolol for treatment of septic shock and hyperthyroidism, respectively. Given persistent hypokalemia despite 2 days of therapy, she was also diagnosed with refeeding syndrome. Discussion: TPP is a rare entity, though it should be considered on the differential for any thyrotoxic patient presenting with sudden weakness. If the associated hypokalemia does not begin to normalize within 48 h of beta blockade, other etiologies should be investigated. Lastly, alternative treatments such as lithium may be used to control hyperthyroidism in patients with methimazole-induced agranulocytosis. Conclusion: While methimazole-induced agranulocytosis and thyrotoxic periodic paralysis are independently rare diagnoses, the combination of the 2 is exceedingly rare, and our case represents the first documented case in the literature reflecting a patient suffering from both syndromes.